1984
DOI: 10.1055/s-2007-969729
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng:Relation between Age of Plant and Content of Ginsenosides

Abstract: The roots of PANAX GINSENG C. A. Meyer contain a relatively high percentage of ginsenosides from their first year of life onwards. Since the major development of weight of roots occurs between the 4th and 5th year of life, it has been established that the highest yield of ginsenosides and therefore the best time for harvesting the roots is at the end of the summer of the 5th year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 4 publications
4
47
1
Order By: Relevance
“…Red and white ginseng powders (less than 200 mesh), supplied by the Korea Ginseng Corporation (formerly, Korean Ginseng and Tobacco Monopoly Corporation in the Republic of Korea), were administered orally at three dose levels (100, 200, and 400 mg/kg/day) in a distilled water suspension. Because the content of sapogenins depends upon the age of the ginseng root (Soldati and Tanaka 1984), we used materials extracted from 6-year-old P. ginseng. Ginseng saponin (25, 50, and 100 mg/kg/day) or non-saponin fractions (50, 100, and 200 mg/kg/day) and pure ginsenosides (Rb 1 , Rg 1 , and Ro) were administered intraperitoneally at three dose levels (2.5, 5, and 10 mg/kg/ day) in an isotonic saline solution because ginsenosides are enzymatically metabolized in the digestive tract of rodents (e.g., Odani et al 1983;Hasegawa et al 1996), particularly by removing glucose.…”
Section: Drug Administrationmentioning
confidence: 99%
“…Red and white ginseng powders (less than 200 mesh), supplied by the Korea Ginseng Corporation (formerly, Korean Ginseng and Tobacco Monopoly Corporation in the Republic of Korea), were administered orally at three dose levels (100, 200, and 400 mg/kg/day) in a distilled water suspension. Because the content of sapogenins depends upon the age of the ginseng root (Soldati and Tanaka 1984), we used materials extracted from 6-year-old P. ginseng. Ginseng saponin (25, 50, and 100 mg/kg/day) or non-saponin fractions (50, 100, and 200 mg/kg/day) and pure ginsenosides (Rb 1 , Rg 1 , and Ro) were administered intraperitoneally at three dose levels (2.5, 5, and 10 mg/kg/ day) in an isotonic saline solution because ginsenosides are enzymatically metabolized in the digestive tract of rodents (e.g., Odani et al 1983;Hasegawa et al 1996), particularly by removing glucose.…”
Section: Drug Administrationmentioning
confidence: 99%
“…Previous work revealed that the fat and mucilage contents varied with age of the roots [3]. Also it was reported that the ginsenoside content and, therefore the therapeutic value of ginseng roots may vary due to their age [4]. Accordingly, the root age should be considered, since the moghat roots available in the markets might be one, two or three years old.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence from previous studies also clearly indicated that Rh 2 and compound K have strong effects on some cultured cancer cells in vitro experiments [13][14][15][16][17][18]. Moreover, it has been reported that ginsenosides in ginseng roots will increase slowly in the first several years and then increase sharply in the fifth and sixth years [19].…”
Section: Discussionmentioning
confidence: 87%